Critical success factors for next generation technical education institutions. Issue 5 (18th February 2019) - Kashiramka, Smita; Sagar, Mahim; Dubey, Amlendu Kumar; Mehndiratta, Amit; , Sushil
Abstract : Purpose: The purpose of this paper is to create a hierarchy of critical success factors affecting the higher technical education institutions, taking a case study of India. Using total interpretive structural modeling (TISM), the paper attempts to establish the inter-linkages among ten critical success factors for enhancing the performance of these institutions. Design/methodology/approach: The paper employs Total Interpretive Structural Modeling (TISM) to understand the hierarchy of the factors and their interplay using response from 18 experts in the domain. Findings: The findings reveal that autonomy and accountability coupled with availability of sustainable funds are the driving factors for the success of the institutions. Infrastructural facilities and establishment of centers of excellence act as amplification factors. Introduction of new programs and their accreditation, improvement in faculty quality, research output and improvement in performance of academically weak students emerge as process factors that drive the output factors, namely, academic performance and student placement. Research limitations/implications: The major limitation of this study is the scope that was limited to 191 institutions, as mandated in the project. Practical implications: This study has important implications for the institutions as well as the policy makers to channelize their focus and efforts on driving and amplification factors that would ultimately lead to enhanced performance of the next generation higher technical education institutions. Originality/value: This paper is a part of pan India project carried out to assess the performance of higher technical education institutions in India.